Forfatterens gjerninger: Upålitelig narrasjon i T.S. Eliots «Journey of the Magi»? - Gaasland, Rolf (Nordlit, 2020)
The article adresses the literary theoretical issue of unreliable narration in first-person fictional narratives. The theoretical discussion is prefaced by an interpretation of T.S. Eliot’s narrative poem “Journey of the Magi”. The interpretation conludes that the narrator, contrary to critical consensus, qualifies as unreliable according to Wayne Booth’s original definition. Having thus opened up the issue of unreliable narration, the article goes on to argue that Booth’s classical definition is misleading, especially when applied to first-person narrators like the one in “Journey of the Magi”. The broader context for the discussion is the question of how narrative fictions communicate and the roles taken by respectively the (real) author and (the fictive) narrator in acts of narrative communication.